TYPES OF GOLD PLACERS OF THE AMYL-SISTIGKHEM PLACER REGION, WEST SAYAN - Ch.M. Khertek; A.M. Sazonov (Минералогия)
Native gold from seven placers of the Amyl-Sistighem ore placer region (the Republic of Tyva, Krasnoyarsk region) is classified on the basis of its structure, morphology and chemical composition, which are studied by optical and electronic microscopy. Three chemical types of native gold are identified: Ag-Au, Hg-Ag-Au, Cu-Ag-Au. There are rounded and angular particles with and without a high-fineness rim. Seventeen types of native gold are established on the basis of combination of various characteristics. These varieties characterize the mineralogical-geochemical types of primary ores, the distance of the transportation of clastic material, the degree of mechanogenic and crystallophysical deformations of gold particles, and the duration of their occurrence in a gold-bearing layer under relatively calm conditions. Our results can be used in planning thematic pre-project and prospecting-assessing work at this territory, whereas methodological issues can be applied in other gold placer areas.